Evaluation of heat flows in axial direction at continuous casting of round billet - E. I. Marukovich; A. M. Branovitskij; Ju. A. Lebedinskij; L. M. Cheshko (Литьë и металлургия, 2003)
On the basis of finite-difference mathematical model for calculation of thermal field of pipe cylindrical continuous casting there is investigated the dispensing of heat flows in lengthwise and radial direction of casting.